EFEKTIFITAS PERATURAN DAERAH KABUPATEN KARANGASEM NOMOR 17 TAHUN 2012 TERHADAP PERTAMBANGAN GALIAN GOLONGAN C DI DESA PEMPATAN KECAMATAN RENDANG KABUPATEN KARANGASEM - Anom, I Gusti Ngurah (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
Mining is considered the most destructive compared to other natural resource exploitation activities, especially mining on sand excavation, since mining work is nothing more than an excavation activity to extract mining objects. Natural resource management including land use for sand mining shall refer to Law Number 32 Year 2009 on Environmental Protection and Management (UU PPLH) and Law Number 4 Year 2009 on Mineral and Coal Mining, together with all other implementing regulations, such as Bali Province Regional Regulation No. 16 of 2009 on Spatial Planning of Bali Province 2009-2029, and Regional Regulation of Karangasem Regency No. 13 of 2012 on Management of Rock Mining Business. Regional Regulation of Karangasem Regency Number 17 Year 2012 About Spatial Planning of Regency of Karangasem Year 2012-2032. Article 71 letter (a) point 1 of the Regional Regulation of Karangasem Regency states